The impact of height-adjustable desks and classroom prompts on classroom sitting time, social, and motivational factors among adolescents - Bronwyn Sudholz; Ana María Contardo Ayala; Anna Timperio; David W. Dunstan; David E. Conroy; Gavin Abbott; Bernie Holland; Lauren Arundell; Jo Salmon (Elsevier, 2023)
Purpose: This quasi-experimental study examined the impact of height-adjustable desks in combination with prompts to break up prolonged sitting time during class time and identified social and motivational factors associated with breaking up sitting time among adolescents. Teachers' perceptions of strategies were also examined. Methods: Over 17 weeks, 1 classroom in a government secondary school in Melbourne, Australia, was equipped with 27 height-adjustable desks and prompts (posters and desk stickers) to break up classroom sitting time. Teachers received professional development in the use of the desks and prompts. One group of adolescents (n = 55) had 2-5 lessons/week using the height-adjustable desks in an intervention classroom, and a comparison group matched by year level and subject (n = 50) was taught in traditional "seated" classrooms. Adolescents wore an activPAL monitor at baseline (T0), 4 weeks (T1), and 17 weeks (T2) and completed a survey at T0 and T2. Six teachers participated in interviews at T2. Effect sizes were calculated (d). Results: Linear mixed models found that, compared to the traditional "seated" classrooms, the adolescents in the intervention classroom had significantly lower sitting time (T1: -9.7 min/lesson, d = -0.96; T2: -6.7 min/lesson, d = -0.70) and time spent in sitting bouts >15 min (T2: -11.2 min/lesson, d = -0.62), and had significantly higher standing time (T1: 7.3 min/lesson, d = 0.84; T2: 5.8 min/lesson, d = 0.91), number of breaks from sitting (T1: 1.3 breaks/lesson, d = 0.49; T2: 1.8 breaks/lesson, d = 0.67), and stepping time (T1: 2.5 min/lesson, d = 0.66). Intervention classroom adolescents reported greater habit strength (d = 0.58), self-efficacy for breaking up sitting time (d = 0.75), and indicated that having a teacher/classmate remind them to stand as helpful (d = 0.50). Conclusion: This intervention shows promise for targeting sitting behaviors in the classroom and indicates that incorporating social and motivational strategies may further enhance outcomes.